Benign prostat hiperplazisine bağlı alt üriner sistem semptomları ile metabolik sendrom ve erektil disfonksiyon arasındaki ilişki - Doğan, Yunus; Uruç, Fatih; Aras, Bekir; Şahin, Aytaç; Kıvrak, Mithat; Ürkmez, Ahmet; Güner, Numan Doğu; Aydın, Sabahattin (AVES, 2015)
Amaç: Benign prostat hiperplazisi (BPH) nedeni ile alt üriner sistem semptomları (AÜSS) olan hastalarda, erektil disfonksiyon (ED) ve metabolik sendrom (MetS) arasındaki ilişkinin belirlenmesi amaçlanmıştır. Gereç ve yöntemler: Polikliniğimize BPH’ya bağlı AÜSS nedeniyle başvuran 40 yaş üstü 78 hasta çalışmaya kabul edildi. Hastalara AÜSS ve ED değerlendirilmesi için sırası ile uluslararası prostat semptom skoru (IPSS), Uluslararası erektil fonksiyon indeksi (IIEF-5) formları dolduruldu. MetS tanısı için the National Cholesterol Education Program Adult Treatment Panel III kriteri kullanıldı. AÜSS, IPSS’a göre hafif, orta ve şiddetli olarak, ED ise IIEF-5 skoruna göre ise hafif, orta-hafif, orta, şiddetli gruplarına ayrılarak incelendi. Bu üç durumun birbirleri ile ve yaşa göre ilişkilerin değerlendirilmesinde Student’s t test, Mann-Whitney U, ANOVA, ki-kare, Fisher Exact testi ve Pearson korelasyon analizi kullanıldı. P<0,05 anlamlı kabul edildi. Bulgular: Çalışmaya katılan hastaların ortalama yaşları 61,83±9,15 bulundu. Olguların %34,6’sında MetS, %70,5’inde ED ve %37,2’sinde şiddetli AÜSS tespit edildi. Yaş gruplarına göre dağılımda yaş ile AÜSS ve ED’nin arttığı görüldü, MetS’nin yaş ile bir ilişkisi bulunmadı. MetS ve bileşenleri ile ortalama IPSS sko- runda ve AÜSS’nin şiddeti arasında istatistiksel olarak anlamlı ilişki görülmedi. Ancak trigliserid düzeyleri ile IPSS skoru arasında zayıf derecede pozitif korelasyon mevcuttu. MetS olan hastalardaki ortalama IIEF koru MetS olmayan hastalardaki skora göre anlamlı dercede daha düşük bulundu. MetS olan hastalarda ED oranı MetS olmayan hastalara göre anlamlı olarak daha fazla bulundu. AÜSS şiddet gruplarındaki ED oranı, şiddetli AÜSS grupta diğer gruplardan istatistiksel olarak daha fazla bulundu. Bununla paralel olarak IIEF skoruyla IPSS skoru arasında zayıf derecede negatif korelasyon saptandı.

Objective: To determine the relationship between erectile dysfunction and metabolic syndrome (MetS) in patients with benign prostatic hyperplasia (BPH) and lower urinary tract symptoms (LUTS). Material and methods: Seventy-eight patients who were admitted to our outpatient clinic because of BPH-related LUTS over 40 years of age were included in the study. Patients with LUTS and erectile dysfunction (ED) were evaluated by International Prostate Symptom Score (IPSS) and International Index of Erectile Function-5 (IIEF-5) forms. The National Cholesterol Education Program Adult Treatment Panel III criteria was used for the diagnosis of MetS. LUTS were classified as mild, moderate, and severe according to IPSS and ED was classified as mild-moderate, moderate, and severe according to the IIEF-5. For the evaluation of data, descriptive statistical methods (mean, standard deviation, median, frequency, ratio, minimum, and maximum) and also for the comparison of the variables with non-normal distribution in 3 or more than 3 groups Student's t test, Mann-Whitney U, ANOVA, chi-square, Fisher Exact tests, and Pearson correlation analysis were used. P<0.05 was accepted as the level of statistical significance. Results: Mean age of the patients included in the study was 61.83 +/- 9.15. In 34.6% of the patients with MetS, 70.5% of the patients with ED and 37.2% of the patients with severe LUTS were determined. There were no significant differences between the mean age of patients with and without metabolic syndrome (p>0.05). There was a positive correlation with age and severity of LUTS but this relationship was not found to be statistically significant (p>0.05). Mean age of the patients with ED was significantly higher than those without (p<0.001). A statistically significant relationship was not observed between the mean IPSS scores and the severity of LUTS with Mets. However, we observed a weakly positive correlation between triglyceride levels and IPSS. Mean IIEF-5 scores of the patients with MetS were significantly lower than those of the patients without MetS. Severity of ED in the patients with MetS was significantly higher than patients without MetS. The percentage of ED in patients with severe LUTS was found to be statistically higher than other patients with mild, and moderate LUTS. In addition, we found a low degree of negative correlation between IPSS and IIEF-5 scores. Conclusion: In patients with LUTS as a consequence of BPH, when severity of symptoms increases, frequency of MetS increases proportionally and severe ED is observed much more frequently.
The relationships between metabolic syndrome, erectile dysfunction and lower urinary tract symptoms associated with benign prostatic hyperplasia
WOS: 000360378600002
PubMed ID: 26328190
Keywords: Erektil Disfonksiyon; Alt Üriner Sistem Semptomları; Metabolik Sendrom; Erectile Dysfunction; Lower Urinary Tract Symptoms; Metabolic Syndrome